Pengaruh Intensitas Aset Biologis, Profitabilitas, Ukuran Perusahaan, dan Kepemilikan Manajerial terhadap Pengungkapan Aset Biologis - Cantika, Mona Ayu; Nurmayanti, Poppy; Afifah, Ulfa (Universitas Prasetiya Mulya, 2023)
This study aims to examine the influence of the intensity of biological assets, profitability, company size, and managerial ownership on the disclosure of biological assets in agricultural companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2021. Based on predetermined criteria using a purposive sampling technique, 42 companies were selected from a population of 130 companies. The results of the study indicate that the intensity of biological assets affects the disclosure of biological assets, but profitability, company size, and managerial ownership do not affect the disclosure of biological assets. Furthermore, the intensity of biological assets, profitability, company size, and managerial ownership did not affect the disclosure of biological assets before the implementation of PSAK 69, according to additional investigations. Then, after the implementation of PSAK 69, the disclosure of biological assets was influenced by the intensity of biological assets and profitability, but not by company size and managerial ownership. The limitation of this study is that it focuses only on four independent variables: the intensity of biological assets, profitability, company size, and managerial ownership. The results of this study indicate that there are additional factors that may influence the disclosure of biological assets.